The ReCLes.pt CLIL project in practice: teaching with results in higher education - Arau Ribeiro, María del Carmen (2018)
Based on the project partially funded by the Portuguese Foundation for Science and Technology (FCT), the ReCLes.pt CLIL initiative created communities of practice and learning for Content and Language Integrated Learning (CLIL) in Higher Education. The project was implemented in six polytechnic institutes in Portugal to support and develop teaching in English based on a methodology that integrates content and language while attending to learners’ needs in both areas. Despite the growing number of English as a Medium of Instruction classes in Higher Education, there remains a paucity of CLIL in the country, both at this and at other levels, although neighboring Spain, for example, has demonstrated an ample use of the CLIL approach, especially in primary and secondary schools. This paper provides an opportunity to get to know these communities of practice and learning in Higher Education to better understand the various ways of dealing with this concept, involving not only the English teachers but also the specific subject teachers in training. This contribution also covers the basis for this training, how the groups are formed, ways to make them work, and best practice as well as results related to monitoring and assessment over the initial three years of the project. The variety of topics and tools created for the 33 piloted modules by these communities of CLIL practice and learning have been published as part of the project. In many cases, continue to be specifically designed and then implemented and assessed in Portuguese Higher Education based on the ReCLes.pt CLIL Training Guide (Morgado et al., 2015).